Demokratisering og populisme: Det latinamerikanske alternativ til nyliberalismen - Jensen, Carsten (Politik, 2013)
According to the political philosopher Ernesto Laclau both Latin American left populists like the newly elected President Nicolas Maduro in Venezuela and European social democrats would bene t from a politi- cal alliance. United they would stand stronger in the challenge to global neoliberalism. is article covers the theoretical and historical back ground to these political ideas in Laclaus works. Especially the role of the concept of Radical Democracy is highlighted. e article questions if di erent views on personal leadership and authoritarian leaders in the third world on the left in Latin America and in Europe will be a barrier to closer cooperation.